ARSTUDIO: estúdio virtual para produção de conteúdos audiovisuais em realidade aumentada para a TV Digital - Sementille, Antonio Carlos [UNESP]; Américo, Marcos [UNESP]; Belda, Francisco Rolfsen [UNESP]; Marar, João Fernando [UNESP]; Cunha, Arielly Kizzy [UNESP] (My University, 2014)
“Virtual Studio” is a system developed for the creation of virtual sets, as well as any threedimensional virtual objects that can be digitally integrated to the scenes captured on a real television studio. Through techniques such as chroma-key, computer graphics , augmented reality and virtual reality is possible flexibility in producing content for digital TV, reduce cost and meet 12.485/2011 law, the Brazilian “Law of Pay TV”, which has among its objectives “to increase the production and circulation of diverse and quality Brazilian audiovisual content, generating jobs, income, royalties, professionalism and strengthening of national culture” (ANCINE , Brazilian Nacional Cinema Agency ). Based on this background, an overview of the benefits of using the technologies mentioned for the production of content for digital television is presented. This work involves the development of a system of Interactive Virtual Studio called ARSTUDIO per team of researchers from the Posgraduate Program in Digital Television: Information and Knowledge at UNESP, São Paulo State University in Bauru, State of São Paulo, Brazil.

“Virtual Studio” es un sistema desarrollado para la creación de escenarios virtuales, así como los objetos virtuales tridimensionales que se pueden integrar digitalmente a las escenas capturadas en un estudio de televisión real. A través de técnicas como el chroma-key, computación gráfica, realidad aumentada y realidad virtual es posible la flexibilidad en la producción de contenidos para la televisión digital, reducir los costos y cumplir con la ley 12.485/2011, la “Ley de la TV de pago” de Brasil, que tiene entre sus objetivos “aumentar la producción y circulación los contenidos audiovisuales brasileños diversa y de calidad, la generación de empleos, renta, royalties, la profesionalidad y el fortalecimiento de la cultura nacional” (ANCINE– Agencia Nacional de Cine). Sobre la base de estos antecedentes, se presenta una visión general de los beneficios del uso de las tecnologías mencionadas para la producción de contenidos para la televisión digital. Este trabajo consiste en el desarrollo de un sistema de estudio virtual interactivo llamado ARSTUDIO por equipo de investigadores del Programa de Posgrado en Televisión Digital: Información y Conocimiento-UNESP, Universidade Estadual Paulista “Júlio de Mesquita Filho” en Bauru, Provincia de São Paulo, Brasil.
Keywords: Augmented Reality; Audiovisual content production; TV Digital; Virtual Studio; Realidad Aumentada; Producción de contenidos audiovisuales